The Ethics of Professional Happiness among Indonesian : Dante Alighieri and Mochtar Lubis on politicians - Guruh David Agus (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2026)
The political profession is a form of vocation, a livelihood by design. In this regard, observing contemporary Indonesia, one might contend -without intent to disparage- that the nation resembles a “house of disorder” inhabited by individuals -including politicians- driven to madness by power, corruption-collusion-nepotism, and the pursuit of position. This study explores alternative religious ideas concerning the ethics of vocational happiness as applicable to today's political actors. Employing content analysis, it contextualizes two figures: Dante Alighieri and Mochtar Lubis as material objects alongside the ethics of professional happiness as a formal object. Ethical Indonesian politicians may find fulfillment through measured prosperity, aesthetic-poetic living, promotion systems rooted in datacracy, and firm revocation of professional licenses for ethical breaches. Dante’s nine infernal circles: limbo, lust, gluttony, greed, wrath, heresy, violence, fraud, and treachery, portray moral descent; while Lubis’s depiction of the Indonesian character exposes hypocrisy, irresponsibility, feudalism, symbolic fixation, weak will, extravagance, and one virtue: artistry. Remarkably, both thinkers resonate with critical, religiously grounded visions that may prove transformative for political vocational ethics in Indonesia.